Bosnia: The Hidden Horrors - Part 1
Correspondent Dave Marsh shows graphic evidence of "ethnic cleansing" by interviewing survivors of the Omarska and Trnopolje camps. Also, Tedd Knoppel interviews Elie Wiesel who received the Peace Nobel Prize in 1986. George Murphy